How Can Covid-19 Affected to Labor Sectors? A Critical Note - Ilham Ma'ruf Arif Legowo (The Indonesian Journal of International Clinical Legal Education, 2020)
Circular of the Minister of Manpower Number M / 3 / HK.04 / III / 2020 concerning Protection of Workers / Laborers and Business Continuity in the Prevention and Countermeasure of COVID-19, especially Part II Point 4 which reads: "For companies that restrict business activities due to government policies in each region for the prevention and control of COVID-19, so that some or all workers / laborers do not come to work, taking into account business continuity, changes in the amount and method of payment of workers / laborers' wages are carried out in accordance with the agreement between employers and workers / laborers. " This is not in accordance with the Manpower Act No. 13 of 2003 because with the issuance of the Minister's Circular the workers 'rights can be arbitrarily violated because the Letter can negotiate workers' rights which is contrary to the Manpower Law and the Letter is not binding on the company which means companies may not implement the Minister of Manpower Circular.